Abdulla Avloni's Great Contributions to the Development of the Field of Pedagogy (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
Using the rich heritage of the great pedagogue-scientist Abdulla Avloni in the process of educating students and studying the scientific heritage of Abdulla Avloni in the development of modern pedagogy.